Nitrogen addition enhances nitrogen but not carbon mineralization in aggregate size fractions of soils in a Pinus massonia plantation - Chen, Tian; Cheng, Ruimei; Xiao, Wenfa; Zeng, Lixiong; Shen, Yafei; Wang, Lijun; Sun, Pengfei; Zhang, Meng; Li, Jing (Frontiers in Forests and Global Change, 2024)
Introduction Atmospheric nitrogen (N) deposition can impact the levels of soil organic carbon (SOC) and total nitrogen (total N) by altering the soil N availability. However, the effect of N input on the mineralization of SOC and total N in various soil aggregate size fractions requires further clarification. Methods The soil samples were collected from a Pinus massoniana plantation situated in the Three Gorges Reservoir Area of China. Over a period of three years, the soils from the plantation were subjected to four different levels of nitrogen addition (0 [N0], 30 [N30], 60 [N60], and 90 [N90] kg N ha−1 yr−1). The impact of N addition on the mineralization of SOC and total N in aggregates was evaluated through an incubation experiment, encompassing four aggregate sizes (2000 − 8000, 1000 − 2000, 250 − 1000, and < 250 μm). Results The < 250 μm fraction showed the highest levels of cumulative C mineralization, while the lowest levels were observed in the 2000 − 8000 μm fraction. Compared to the < 250 um fraction, a drop of 9 − 21% in cumulative C mineralization was observed in the 2000 − 8000 μm fraction, indicating that soil aggregates enhance the stability of C in the soil. Cumulative N mineralization levels were consistently at their lowest in the 2000 − 8000 μm fraction, indicating aggregates reducing mineralization-related N loss. Adding N to forest soil samples led to a reduction in cumulative C mineralization. In contrast, an opposite trend was observed in the cumulative N mineralization after adding N in microaggregates. Nitrification was the main contributor to net N mineralization. SOC and total levels increased in response to N30 and N60. N addition leads to an increase in the weight ratio of the 1000 − 2000 μm fraction. Moreover, N90 was linked to decreases in microbial biomass C and N. Discussion These findings confirm that the structural characteristics of soil aggregates play a crucial role in sequestering organic carbon and total N sequestration in the presence of N deposition, while highlighting N loss from the soil caused by N input.